Implementasi Nilai-Nilai Pendidikan Agama Islam di Era Modern - Kevin Maulana Al Ghafar; Muhammad Oriza Pradana; Izzul Nurdin Setyawan (Yayasan Literasi Sains Indonesia, 2026)
The transformation of Islamic Religious Education (PAI) in the digital era is currently confronted with multifaceted challenges, primarily the escalation of moral degradation and identity crises triggered by the pervasive integration of technology and Artificial Intelligence (AI). This study aims to critically analyze and formulate strategic frameworks for implementing PAI values that remain adaptive to modern demands while preserving the ontological essence of spirituality and character integrity. Employing a Systematic Literature Review (SLR) methodology, this research synthesized 20 high-quality scientific articles published within the last five years to ensure data actuality and relevance. The analysis proposes a